Monodisperse Ca 0.15Fe 2.85O 4 microspheres: Facile preparation, characterization, and optical properties - Shen, Y.; Zhao, Q.; Li, Xin Yong; Zhang, D. (2012)
Micro/nanospheres have been intensively investigated recently because of their attractive applications. While long reaction times, harsh reaction conditions or multiple steps are generally required for the effective synthesis of ferrites, in this study, Ca 0.15Fe 2.85O 4 microspheres were successfully fabricated via a facile one-pot solvothermal method, utilizing polyethylene glycol as a surfactant. XRD, HRTEM, and SEM analysis revealed that the Ca 0.15Fe 2.85O 4 microspheres prepared were monodisperse in nature, with uniform diameters of about 450 nm and porous interior structure. The Ca 0.15Fe 2.85O 4 microspheres exhibited a clear absorption capacity in the visible light region and the band-gap energy was about 1.95 eV. Furthermore, photovoltaic response of the Ca 0.15Fe 2.85O 4 microspheres was shown in the UV-Visible spectral region, due to the effective photo-induced charge carrier separation. The Ca 0.15Fe 2.85O 4 microspheres may find potential applications in many fields, such as photocatalysis, photovoltaics, sensors, optical, and biomedical devices. © 2011 Springer Science+Business Media, LLC.